Why do firms issue callable convertible bonds? A critique of the “backdoor equity financing” theory - Burlacu, Radu; Jimenez-Garcès, Sonia (Journal of Banking & Finance, 2022)
We revisit Stein (1992)’s model and demonstrate that it provides an insufficient justification for the use of callable convertible bonds as financing instruments. A standard convertible bond solves the firm’s financing problem in both the simple and extended versions of the model. More generally, convertibles have little relevance within this model because the firm can finance efficiently with a package of equity and short-term straight debt, the components of which are dynamically adjusted. This package becomes a superior financing strategy in comparison to convertible debt if one relaxes the model’s assumption that the firm can always force conversion.